2003
DOI: 10.1081/etc-120020462
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and Testing for Unit Root Processes with GARCH (1, 1) Errors: Theory and Monte Carlo Evidence

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 26 publications
0
27
0
1
Order By: Relevance
“…With regard to the impact of neglected GARCH on the (augmented) Dickey-Fuller (ADF, Dickey and Fuller 1979) test, see, e.g., Kim and Schmidt (1993), Ling and McAleer (2003) and the literature they refer to. Due to the invariance principle, the ADF test proves to be asymptotically robust to covariance stationary GARCH errors.…”
Section: Testing For Integrated Interest Rate Spreadsmentioning
confidence: 99%
“…With regard to the impact of neglected GARCH on the (augmented) Dickey-Fuller (ADF, Dickey and Fuller 1979) test, see, e.g., Kim and Schmidt (1993), Ling and McAleer (2003) and the literature they refer to. Due to the invariance principle, the ADF test proves to be asymptotically robust to covariance stationary GARCH errors.…”
Section: Testing For Integrated Interest Rate Spreadsmentioning
confidence: 99%
“…This implies that conventional DF tests for a unit root will be asymptotically valid, even though more powerful tests can be obtained by explicitly modelling the volatility process; see, e.g., Seo (1999) and Ling et al (2003).…”
Section: The Model and Preliminary Resultsmentioning
confidence: 99%
“…This was illustrated using Monte Carlo simulations by Kim and Schmidt (1993). However, subsequent research has indicated that in such cases more powerful tests for a unit root may be obtained from a likelihood analysis of a model with GARCH innovations; see Seo (1999) and Ling et al (2003), based on Ling and Li (1998), inter alia.…”
Section: Introductionmentioning
confidence: 99%
“…Many theories for inference for unit root models with GARCH errors are readily available. For example, [10] considers the least squares and maximum likelihood estimation for unit root processes with GARCH(1,1) errors; [9] investigates the one-step local quasi-maximum likelihood estimator for the unit root processes with GARCH(1,1) errors. The asymptotic distributions of the estimators in both papers are derived under the condition that Eu 2 t < ∞ and Ez 4 t < ∞.…”
Section: §1 Introductionmentioning
confidence: 99%